2009
DOI: 10.1007/s10549-009-0439-5
|View full text |Cite
|
Sign up to set email alerts
|

The Fanconi anemia family of genes and its correlation with breast cancer susceptibility and breast cancer features

Abstract: International audienceFanconi anemia (FA) family of proteins participates in the DNA repair pathway by homologous recombination, and it is currently formed by 13 genes. Some of these proteins also confer susceptibility to hereditary breast and ovarian cancer (HBOC), since is the breast cancer susceptibility gene, and and explain 2% of non-BRCA1/2 HBOC families. Thus, there is an important connection between FA and BRCA pathways. In a previous case–control association study analysing , and , we reported an asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Though the loss of expression of PTEN, P53, ATM and CHK2 genes had been identified to correlate with some sporadic breast cancers, they neither have specificity in diagnosis nor can provide clinical therapeutic guidance [9][10][11][12] . In recent study, it was found that 19% sporadic breast cancers lost the expression of FANCD2 gene, which suggested that FANCD2 may be an independent prognostic factor for sporadic breast cancer [13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Though the loss of expression of PTEN, P53, ATM and CHK2 genes had been identified to correlate with some sporadic breast cancers, they neither have specificity in diagnosis nor can provide clinical therapeutic guidance [9][10][11][12] . In recent study, it was found that 19% sporadic breast cancers lost the expression of FANCD2 gene, which suggested that FANCD2 may be an independent prognostic factor for sporadic breast cancer [13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 20 case-control studies were discerned. However, three studies were excluded because of insufficient data (Barroso et al, 2009;Rendleman et al, 2014;Hayashi et al, 2015). Two studies used the same data, so only one of them was included (Pharoah et al, 2007;Yang et al, 2014).…”
Section: Extraction Process and Study Characteristicmentioning
confidence: 99%
“…As the majority of these miRNAs binds to the 3'UTR region of the genes (Sehl et al, 2009), variations in the 3'UTR regions of BRCA1/2 may also affect the regulation of related proteins and thus response to the applied therapy (Nilsen, 2007). In addition, the importance of miRNA-binding site single-nucleotide polymorphisms (SNPs) of the BRCA1/2 genes in breast and ovarian cancer has been emphasized in recent studies of certain individual populations (Barroso et al, 2009;Pongsavee et al, 2009;Sehl et al, 2009;Kontorovich et al, 2010;Nicoloso et al, 2010;Joseph et al, 2011). However, knowledge about the effect of 3'UTR site variations of BRCA1/2 remains elusive.…”
Section: Introductionmentioning
confidence: 99%